Between rites and contexts: Decisions and meanings attached to natural childbirth humanized - Bárbara Régia Oliveira de Araújo; Maria Cristina Soares Figueiredo Trezza; Regina Maria dos Santos; Larissa Lages Ferrer de Oliveira; Laura Maria Tenório Ribeiro Pinto (Universidad de Alicante, 2019)
The object of this study is the development of decisions and meanings assigned by women from different health contexts in humanized natural birth. This is a qualitative and descriptive study based on stories of 14 women from Maceió/AL, Brazil. To generate reports it was used an interview form based in the Transcultural Nursing Theory from Madeleine Leininger. The results highlight two groups: A) Women that wished a humanized natural birth; and, B) Women that didn´t wish a humanized natural birth. The first group did so believing in maternal-fetal benefits and also wishing to exercise their autonomy, giving birth respectfully through a violence free health care; while the women in the second group reported different reasons for their choices, whether understanding the shortcomings from national health system or even from fear of pain and easy access to elective cesareans. It is understood that the meanings and decisions made by the informants about their parturition are closely related with their contexts and the understanding of their health-disease process linked to parturition.